Correction: Patching, S.G. Spermidine Binding to the Acetinobacter baumannii Efflux Protein AceI Observed by Near-UV Synchrotron Radiation Circular Dichroism Spectroscopy. Radiation 2022, 2, 228–233 - Radiation Editorial Office (Radiation)
Radiation’s Editorial Office wishes to make the following changes to the published article [...]